Ответы и объяснения

2013-09-22T15:38:01+00:00
Tg(x/2)=(sinx-2cosx)/(sinx+2cosx) 

выразим всё через tg(x/2) 
sinx=2tg(x/2)/(1+(tg(x/2))^2) 
cosx=(1-(tg(x/2))^2)/(1+(tg(x/2))^2) 

sinx-2cosx=2tg(x/2)/(1+(tg(x/2))^2)-2*(1-(tg(x/2))^2)/(1+(tg(x/2))^2)=(2tg(x/2)-2+2*(tg(x/2))^2)/(1+(tg(x/2))^2) 
sinx+2cosx=2tg(x/2)/(1+(tg(x/2))^2)+2*(1-(tg(x/2))^2)/(1+(tg(x/2))^2)=(2tg(x/2)+2-2*(tg(x/2))^2)/(1+(tg(x/2))^2) 

tg(x/2)=(2tg(x/2)-2+2*(tg(x/2))^2)/(2tg(x/2)+2-2*(tg(x/2))^2) 
tg(x/2)=(tg(x/2)-1+(tg(x/2))^2)/(tg(x/2)+1-(tg(x/2))^2) 
tg(x/2)-1+(tg(x/2))^2=tg(x/2)*(tg(x/2)+1-(tg(x/2))^2) 
tg(x/2)-1+(tg(x/2))^2=(tg(x/2))^2+tg(x/2)-(tg(x/2))^3 
-1=-(tg(x/2))^3 
(tg(x/2))^3=1 
tg(x/2)=1 
x/2=пи/4+пи*k 
x=пи/2+2*пи*k, k - целые числа